High-Dose Methotrexate-Induced Idiopathic Intracranial Hypertension in Infant Acute Lymphoblastic Leukemia - Zhang, Yazhi; Qiu, Yining; Wang, Zhujun; Wang, Ran; Jin, Runming; Hinkle, Louis Edward; Wu, Xiaoyan (Frontiers in Pharmacology, 2020)
A 7-month-old baby girl with acute lymphoblastic leukemia (ALL) presented with continuous anterior fontanelle uplift without abnormal laboratory and imaging investigation at the same day after completing the first or second courses of high-dose methotrexate (HD-MTX) chemotherapy. Between the intermission of the courses, the infant recovered and timely discharge. Prior to the third and fourth HD-MTX courses, the baby girl was received the infusion of dexamethasone and did not present side effects once again. To our knowledge, this is the first case of HD-MTX induced idiopathic intracranial hypertension in infants, and prophylactic use of dexamethasone could be applied for preventing foreseeable acute intracranial hypertension of HD-MTX infusion.